Integrity in the age of AI: navigating authorship, accountability and ethical publishing - Yulingga Nanda Hanief (Physical Education and Sports: Studies and Research, 2026)
The rapid emergence of generative artificial intelligence (AI) is reshaping the landscape of academic writing and scholarly publishing, offering both opportunities and ethical challenges. This editorial reflects on the growing implications of AI-assisted authorship, particularly regarding authorship, accountability, and research integrity. While AI tools can improve clarity and accessibility, their misuse raises concerns about the erosion of critical thinking and the reliability of scientific results. A key issue highlighted in this discussion is the increasing incidence of false or unverifiable references generated through AI-assisted processes. These practices threaten the credibility of scholarly communication and increase the burden on editors and reviewers. In response, this editorial emphasizes the importance of responsible AI use, transparency in authorship, and rigorous source verification. Furthermore, the article outlines the journal's commitment to maintaining high standards of quality and ethical publishing. This includes strengthening editorial policies, promoting integrity in manuscript preparation, and encouraging accountability among authors. The editorial also calls on the academic community to adopt responsible practices in the use of emerging technologies. In line with international publishing standards, this editorial is designed to provide critical perspectives, articulate editorial responsibilities, and offer a forward-looking stance on ethical scientific communication. Ultimately, maintaining trust and credibility in the AI era requires a collective commitment to transparency, rigor, and integrity at every stage of the publication process.